Common Poisonous Weed and Invasive Plant Species in Florida Residential Landscapes - Yuvraj Khamare; Chris Marble (EDIS, 2022)
This new 10-page publication of the UF/IFAS Environmental Horticulture Department is intended to inform home gardeners, pest management professionals, and other plant enthusiasts of some of the most common poisonous invasive plants or weed species common in home landscapes in Florida, with particular focus on species that could potentially cause harm if ingested. Written by Yuvraj Khamare and Chris Marble. https://edis.ifas.ufl.edu/ep631